Constructive communication in contexts of complexity : a case study of the wolf conflict in Sweden - Cederlöf, Lina (SLU/Dept. of Urban and Rural Development, 2015)
Many societal issues of today are characterized by complexity and conflicts, which often arise as a consequence of multiple actors with divergent perspectives. The on-going wolf conflict in Sweden is one example of an issue commonly perceived as complex and with increasing polarization. The conflict is reflected in public communication about the issue where epithets such as ‘wolf huggers’ and ‘wolf haters’ are pitted against each other. By using the wolf conflict as a case, this study aims to explore approaches and experiences related to communication in wicked issues in order to reveal underlying factors, which may contribute to or inhibit constructive communication. The case study is informed by a theoretical framework, which draw from a broad understanding of the characteristics of wicked issues and further, through Habermas critical theory, positions such issues in relation to dilemmas of modern society. Jordan’s awareness theory gives an operationalized view from organizational theory. A phenomenological approach is applied and the empirical material was collected through 11 in-depth semi-structured interviews with respondents from five different NGOs active within the domain of the issue. Empirical findings from the study are presented in five themes: (1) Conceptualizations of complexity, (2) Arenas for communication, (3) Conceptualizing goals for communication, (4) Perceptions of science and facts in communication, and (5) Multiple roles. Underlying factors inhibiting constructive communication, appeared to pertain to (a) overreliance on scientific authority, (b) ‘othering’ of opponents, (c) communication as one way transmission of information with educative or strategic goals, (d) dramaturgy of media and (e) competitiveness of debate. The study opens up for discussion and further inquiry on how NGOs, management processes and arenas for communication can become better in supporting development of complexity awareness and constructive communication praxis.